Breathing Life into the Earth: Experience-Based Oxygen Education Through a Tree-Planting Initiative at Elementary Schools - Taufikin Taufikin (BASICA, 2024)
Oxygen sustains life, yet in elementary education, it is often treated as an abstract concept detached from real-world experience. This study examines how understanding of oxygen is constructed through tree-planting activities. The approach used was a qualitative case study, with data collected through participant observation, in-depth interviews, and documentation from October to December 2023 in SD Negeri Harjowinangun 02 Dempet Demak. The results reveal a multi-layered transformation. On the cognitive dimension, students transitioned from a general understanding to recognising the cause-and-effect relationship between trees and oxygen. On the affective dimension, emotional engagement emerged in the form of ecological concern and empathy. On the social dimension, collective responsibility was fostered through collaborative practices and social control. These three dimensions are integrated into a single experience-based learning process. These findings confirm that concrete experiences serve as an epistemic bridge connecting scientific concepts with living ecological awareness. The novelty of this research lies in the development of oxygen-based ecological pedagogy as an integrative model that unites experience, reflection, emotion, and social practice. This model expands science learning toward contextual practice and strengthens sustainable environmental education